Basal forebrain degeneration precedes and predicts the cortical spread of Alzheimer’s pathology - Taylor W. Schmitz (Nature Portfolio, 2016)
Whether Alzheimer’s disease originates in basal forebrain or entorhinal cortex remains highly debated. Here the authors use structural magnetic resonance data from a longitudinal sample of participants stratified by cerebrospinal biomarker and clinical diagnosis to show that tissue volume changes appear earlier in the basal forebrain than in the entorhinal cortex.